Portuguese as an Additional Language, teaching and culture: reflections on teacher education for mediation and cultural sensitivity - Heitor Sampaio, Glauber Heitor; Rodrigues, Luana (BELT - Brazilian English Language Teaching Journal, 2019)
This article presents the results of a research that sought to investigate and discuss the experience of a group of PLA (Portuguese as an Additional Language) student-teachers while working at an extension course and their training to approach cultural themes within a conception of cultural mediation (Manaa, 2009). This research was based on a qualitative and interpretative approach whose focus was on recognizing, analyzing and understanding the way cultural knowledge is developed taking into account the teaching of foreign language, cultural diversity, and cultural intermediation. Data was generated through written narratives and the analysis was conducted in a way to identify the perception of the studentteachers about their own approaches and readiness towards cultural mediation on a daily basis. As a result, we concluded that, although not realizing that they have undergone training to such issues (cultural education, interculturality, and cultural mediation), they are able to reflect, position themselves and mediate cultural themes in a sensitive manner.